2019
DOI: 10.1177/2049463719858119
|View full text |Cite
|
Sign up to set email alerts
|

Brief cognitive analytic therapy for adults with chronic pain: a preliminary evaluation of treatment outcome

Abstract: Background: Cognitive analytic therapy (CAT) has diversified in its application to a broad range of presenting difficulties and formats and there has been growing interest in its use in clinical health settings including Pain Management Services. Despite its growing popularity, to date, no studies have examined the application of CAT for chronic pain. Aims: The purpose of this study was to examine the effectiveness of time-limited, individual CAT for adults with chronic pain as delivered in a publicly funded C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
(58 reference statements)
0
3
0
Order By: Relevance
“…This recent review also highlighted the relative lack of evidence for the 8-session version of the model (i.e., only 2 of the 28 studies in the narrative review evaluated 8session CAT; one RCT and practice-based study in a pain management service) and also the urgent need to increase evidence of effectiveness with anxiety and depression. Baronian and Leggett (2019) piloted an 8-session CAT protocol in a pain management service, finding that 28% of the N = 53 sample had a reliable and clinically significant reduction in distress. Furthermore, a recent study showed that 8-session CAT was an effective treatment for obsessive morbid jealousy.…”
mentioning
confidence: 99%
“…This recent review also highlighted the relative lack of evidence for the 8-session version of the model (i.e., only 2 of the 28 studies in the narrative review evaluated 8session CAT; one RCT and practice-based study in a pain management service) and also the urgent need to increase evidence of effectiveness with anxiety and depression. Baronian and Leggett (2019) piloted an 8-session CAT protocol in a pain management service, finding that 28% of the N = 53 sample had a reliable and clinically significant reduction in distress. Furthermore, a recent study showed that 8-session CAT was an effective treatment for obsessive morbid jealousy.…”
mentioning
confidence: 99%
“…Chronic pain (CP) is the main cause of suffering and disability in the world ( Salduker et al, 2019 ; Treede et al, 2019 ; Baronian and Leggett, 2020 ), affecting 19% of Europeans ( Breivik et al, 2006 ). In Portugal, this condition is particularly prevalent as it affects 37% of the population ( Azevedo et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…This issue of the British Journal of Pain demonstrates the diversity in pain research and contains papers that will be of interest to practitioners from many disciplines covering a diverse range of topics from best practice in radiofrequency denervation procedures, 2 the cerebral effects of paracetamol, 3 cognitive analytical therapy, 4 to the importance of communication in postsurgical pain. 5…”
mentioning
confidence: 99%